2013
DOI: 10.1093/beheco/art052
|View full text |Cite
|
Sign up to set email alerts
|

Predator and prey activity levels jointly influence the outcome of long-term foraging bouts

Abstract: Consistent interindividual differences in behavior (i.e., "behavioral types") may be a key factor in determining the outcome of species interactions. Studies that simultaneously account for the behavioral types of individuals in multiple interacting species, such as predator-prey systems, may be particularly strong predictors of ecological outcomes. Here, we test the predator-prey locomotor crossover hypothesis, which predicts that active predators are more likely to encounter and consume prey with the opposin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 51 publications
1
42
0
Order By: Relevance
“…The “locomotor crossover hypothesis” predicts that active/bold predators tend to capture inactive/shy prey, whilst inactive/shy predators tend to capture active/bold prey34. This has been supported by empirical studies on a system consisting of black turban snails ( Chlorostoma funebralis ) and their predator sea stars ( Pisaster ochraceus ) as well as in another system composed of crickets ( Acheta domesticus ) and their predator jumping spiders ( Phidippus clarus )3132. However, inconsistent with the locomotor crossover hypothesis, bolder crickets ( Gryllus integer ) have higher mortality when encountering bolder black widow spiders ( Latrodectus hesperus )33.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…The “locomotor crossover hypothesis” predicts that active/bold predators tend to capture inactive/shy prey, whilst inactive/shy predators tend to capture active/bold prey34. This has been supported by empirical studies on a system consisting of black turban snails ( Chlorostoma funebralis ) and their predator sea stars ( Pisaster ochraceus ) as well as in another system composed of crickets ( Acheta domesticus ) and their predator jumping spiders ( Phidippus clarus )3132. However, inconsistent with the locomotor crossover hypothesis, bolder crickets ( Gryllus integer ) have higher mortality when encountering bolder black widow spiders ( Latrodectus hesperus )33.…”
mentioning
confidence: 93%
“…Indeed a handful of studies have revealed the joint effects of personality types of both predators and prey on predator foraging performance and prey survivorship313233. The “locomotor crossover hypothesis” predicts that active/bold predators tend to capture inactive/shy prey, whilst inactive/shy predators tend to capture active/bold prey34.…”
mentioning
confidence: 99%
“…Much prior work has related animal personality to various aspects of individuals' ecology (Johnson et al, 2015; Sih et al, 2012; Wolf & Weissing, 2012), such as their body condition (Johnson, Miles, Trubl, & Hagenmaier, 2014; Wright, Keiser, & Pruitt, 2016) and social niche (Laskowski & Pruitt, 2014), by examining only one personality trait at a time (Smith & Blumstein, 2008; Sweeney et al, 2013). Here we used a multitrait approach to examine whether the behavioural hypervolumes occupied by groups of individuals shaped both intraspecific and interspecific interactions.…”
Section: Discussionmentioning
confidence: 99%
“…A growing number of studies has shown that animal personality can predict the outcome of interspecific interactions (Keiser, Slyder, Carson, & Pruitt, 2015; Lichtenstein, Pruitt, & Modlmeier, 2015; Royauté & Pruitt, 2015; Sweeney et al, 2013; Toscano & Griffen, 2014). We found that katydid behavioural hypervolume was negatively correlated with froghopper survival rates (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, active predators often primarily consume inactive prey, while sedentary predators tend to consume active prey [43 ]. Thus, the profitability of exhibiting any particular personality type in either predator or prey depends on personality types present in the interacting trophic level as well as within their own trophic level.…”
Section: Species Interactionsmentioning
confidence: 99%